2018
DOI: 10.1098/rsos.171398
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic niche reflects stress-induced variability in physiological status

Abstract: The isotopic niche has become an established concept in trophic ecology. However, the assumptions behind this approach have rarely been evaluated. Evidence is accumulating that physiological stress can affect both magnitude and inter-individual variability of the isotopic signature in consumers via alterations in metabolic pathways. We hypothesized that stress factors (inadequate nutrition, parasite infestations, and exposure to toxic substances or varying oxygen conditions) might lead to suboptimal physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 66 publications
0
42
0
Order By: Relevance
“…It is important to note that stable isotope signatures may be confounded by environmental stressors unrelated to changes in diet, potentially leading to inaccurate depictions of trophic niche space (Karlson, Reutgard, Garbaras, & Gorokhova, 2018). A study of freshwater snails showed that high temperatures, such as those experienced by temperate species along their trailing range edge, may enrich δ 15 N and δ 13 C values (Ek, Karlson, Hansson, Garbaras, & Gorokhova, 2015).…”
Section: Nevertheless Niche Segregation (Based On Isotopic Niche Spamentioning
confidence: 99%
“…It is important to note that stable isotope signatures may be confounded by environmental stressors unrelated to changes in diet, potentially leading to inaccurate depictions of trophic niche space (Karlson, Reutgard, Garbaras, & Gorokhova, 2018). A study of freshwater snails showed that high temperatures, such as those experienced by temperate species along their trailing range edge, may enrich δ 15 N and δ 13 C values (Ek, Karlson, Hansson, Garbaras, & Gorokhova, 2015).…”
Section: Nevertheless Niche Segregation (Based On Isotopic Niche Spamentioning
confidence: 99%
“…Isotopic niche size is also related to nutritional status, typically expanding when animals encounter stressful environments such as limited resource availability, and retracting in benign environments [120,121,124]. For example, Karlson et al [125] demonstrated that nutritional stress, parasite infestation, and toxin contamination all resulted in larger carbon-nitrogen isotope niches in the marine amphipod Monoporeia affinis, with nutritional stress producing the largest absolute change in isotopic niche space.…”
Section: Inferring Past and Present Nutritional Status From Turnovermentioning
confidence: 99%
“…Among the numerous studies examining how a range of nutritional stresses affect isotopic compositions of various animals, enrichment in 15 N is the response most likely to confound interpretations of isotopic niches, particularly given that isotopic niche metrics rely on the assumption that interindividual variability in enrichment between consumer and prey is insignificant (Karlson, Reutgard, Garbaras, & Gorokhova, ; McCue & Pollock, ). One experiment‐based study on the amphipod Monoporeia affinis revealed wider niche widths among specimens exposed to nutrient and chemical stress relative to control animals (Karlson et al, ). It is understood that increases in isotopic niche areas are a function of interindividual variability in the responses of consumers to stress exposure through changes in their metabolic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…One experiment-based study on the amphipod Monoporeia affinis revealed wider niche widths among specimens exposed to nutrient and chemical stress relative to control animals (Karlson et al, 2018).…”
Section: Limacina Diet May Include Other Taxa When the Preferred Preymentioning
confidence: 97%
See 1 more Smart Citation